The Role and Strategy of School Principals in Implementing Academic Supervision - Hartawan, Roli Fola Cahya; Kosasih, Fitriyani (International Journal of Social Learning (IJSL), 2024)
Academic supervision is an important process in improving the quality of teacher performance. However, in its implementation, there is still a paradigm of thinking that only places academic supervision to fulfill the Principal’s managerial duties. This study explores Principal academic supervision's various roles and strategies in sustainably improving teacher performance. This study used a qualitative approach with a purposive sampling technique. The results showed three important things in conducting academic supervision. First, academic supervision is carried out systematically, starting from the stages of planning (Plan), implementation (Do), evaluation (Check), and follow-up (Act). Second, it is carried out consistently. Third, follow-up recommendations are decided based on relevant teacher performance data-based assessments. In conclusion, the Principal has carried out academic supervision but has not been optimal in the follow-up. Follow-up recommendations on the results of academic supervision have not been implemented sustainably and data-based. As a result, the results of academic supervision have not been able to improve teacher performance and student learning outcomes.